2011
DOI: 10.4102/sajbm.v42i3.495
|View full text |Cite
|
Sign up to set email alerts
|

Structuring effective copreneurial teams

Abstract: Despite growing numbers and increased research attention, few empirical studies have focused on copreneurial family businesses, and hardly any guidelines exist on how these couples should manage their marriage and business relationships. Against this background the primary objective of this study was to empirically assess the influence of selected structural-based factors on the effectiveness of South African copreneurships. The teamwork literature proposes that the success of a team depends on how the team is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…In the context of family business-IPOs, Mazzola and Marchisio (2002) found that after high growth periods, short-term profitability would decrease in the light of the massive investments made to sustain growth. On the contrary, in the context of copreneurial teams, Farrington et al (2011) found that firm growth helps increase financial performance.…”
Section: Business Antecedents and Outcomesmentioning
confidence: 98%
See 2 more Smart Citations
“…In the context of family business-IPOs, Mazzola and Marchisio (2002) found that after high growth periods, short-term profitability would decrease in the light of the massive investments made to sustain growth. On the contrary, in the context of copreneurial teams, Farrington et al (2011) found that firm growth helps increase financial performance.…”
Section: Business Antecedents and Outcomesmentioning
confidence: 98%
“…Literature in the field reinforces the thought that the absence of conflicts and the presence of harmony have a positive effect on firm growth. Broadly defined, family harmony entails family support, goal alignment, stewardship behaviors and altruism (Farrington et al ., 2011; Jamaluddin and Dickie, 2011; Patel et al ., 2012). Family support, via a participative decision‐making style, is recognized as a factor enhancing firm growth: involving family members in constructive business discussions boosts confidence in formulating growth strategies (Jamaluddin and Dickie, 2011).…”
Section: Firm Growth In Family Firmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Deacon, Harris, and Worth (2014) discuss equality between copreneurs, asserting that the skills, responsibilities, and roles of the female and male partners are often complementary and thus create value not only for the business but also for the family. A crucial factor required for concurrent business and marriage success is role clarity between wife and husband (Farrington, Venter, Eybers, & Boshoff, 2011).…”
Section: Overview Of Prior Researchmentioning
confidence: 99%
“…Thus, no partner's contribution was deemed more valuable than the other. The effects on start-up performance in terms of achieving first sales differ in that couples are more likely than other teams to achieve first sales, while the opposite is true for blood-related teams Hedberg & Danes (2012) Examine the dynamic power processes within copreneurial couples as a bridge between entrepreneurship and family firm research Findings illustrate the foundational role of an inclusive power structure and suggest that copreneurial businesses where spouses are seen as equal partners engaging in collaborative power interactions are likely to result in a more productive business decision team that has the resilience to creatively solve important business problems Farrington et al (2011) Empirically assess the influence of selected structuralbased factors on the effectiveness of South African copreneurships Teamwork literature 380 questionnaires completed by individual spouses Results suggest that the success of a marriage between copreneurs is not influenced by the success of the business, but that the more structural elements such as leadership, needs alignment and role clarity are in place, the more satisfied the spouses are likely to be with both their business and their marital relationship Fletcher (2010) Explore the ways in which venture creation is constructed between co-habiting couples Family business literature, entrepreneurship 26 co-preneurial situations A typology of co-preneurship is developed, using ownership and management structural dimensions. This typology is illustrated with different types of lifestyle businesses to demonstrate the economic assessments and 'market work' that give rise to family entrepreneurship.…”
Section: Analytical Hierarchy Process Of Prior Publicationsmentioning
confidence: 99%